DEMOCRACY AS AN ECONOMIC GOOD: A HOLISTIC APPROACH - Gylys, Povilas (Ekonomika, 2012)
Abstract. In orthodox economic theory, democracy is treated as a non-economic phenomenon. Such an attitude is a logical consequence of the individualistic perception of social reality. Methodological individualism is based on the assumption that the only social actor is a separate individual with his self-interest. Consequently, there are no supra-individual, collective actors in social life. Accordingly, economy is equal to the market, and therefore public interests, public needs and other public phenomena are somewhat alien to economy. For individualistic thinkers, one of such non-economic phenomena is democracy, which is the concept of political science and does not belong to the scope of economic science. We argue that methodological individualism gives a distorted picture of economic reality and that a holistic paradigm should be applied in economic inquiry. In the framework of a holistic paradigm, democracy could be treated as an economic good created in the conditions of limited of resources. Moreover, it is an economic good of systemic character, and failures in producing, providing democratic regimes lead to systemic crises. The latter means the spread of anti-economic practices and substantial economic losses.